Ontology construction: cooking domain - Batista, F.; Paulo, J.; Mamede, N.; Ribeiro, R.; Vaz, Paula Cristina (Ontology construction: cooking domain, 2006)
This paper describes an ontology for the cooking domain, reporting on the ontology building process, its life cycle, applied methodologies, taken decisions and achieved results. In the past, our research group built a generic dialogue system able to manage specific devices at home, such as TVs, lamps and windows. The cooking domain appeared as an interesting research area, where our technologies could be applied, and techniques could be explored in order to make the system more independent from new domains. The information in the field is vast, and no information could be found in a manner that we could provide for the system. Besides the process of collecting all information, we also became conscious that techniques for managing and organizing such knowledge were essential. The promising and emerging ontologies domain seemed the best compromise, which was the motivation for developing the ontology here presented. The paper gives details on the steps performed for the building process, which mainly consisted in: specification, knowledge acquisition, conceptualization, implementation and evaluation. The sources of information, used in the knowledge acquisition phase, consisted mainly of books, the internet, and text analysis techniques, as well as brainstorming and cross-validation sessions. Conceptualization consisted on the identification of concepts and groups of concepts and in building classification trees. The knowledge model was formalized using Protégé, which was also used to automatically generate the ontology code. The resulting ontology comprehends four main modules covering the key concepts of the cooking domain – actions, food, recipes, and utensils – and two auxiliary modules units, measures, and equivalencies. All modules were cross-validated in several meetings and informal competency questions were used in order to check the usefulness of the ontology.